Silver-catalyzed synthesis of β-fluorovinylphosphonates by phosphonofluorination of aromatic alkynes - Zhang, Yajing; Tian, Qingshan; Zhang, Guozhu; Zhang, Dayong (Beilstein Journal of Organic Chemistry, 2020)
A silver-catalyzed three-component reaction involving alkynes, Selectfluor®, and diethyl phosphite was employed for the one-pot formation of C(sp2)–F and C(sp2)–P bonds to provide an efficient access to β-fluorovinylphosphonates in a highly regio- and stereoselective manner under mild reaction conditions. This reaction is operationally simple and offers an excellent functional group tolerance as well as a broad substrate scope that includes both terminal and internal alkynes. The reaction proceeded through the oxidative generation of a P-centered radical and subsequent fluorine atom transfer.
Keywords: β-fluorovinylphosphonates; fluorine atom transfer; P-centered radical; silver catalysis; three-component reaction